IMPLEMENTATION OF SIMPLESCALAR PORTABLE INSTRUCTION SET ARCHITECTURE (PISA) ON FPGA - ABDULLAH, ABDUL AZIM (Universiti Teknologi Petronas, 2006)
This report describes the current progress of final year project entitled Implementation of SimpleScalar Portable Instruction Set Architecture (PISA) on FPGA. The objectives of this study are to learn computer system architecture, to sharpen skill in programming and debugging a program and to complete study in Universiti Teknologi PETRONAS. Problem statements will explain the reasons behind of this study was conducted. Firstly, there are few microprocessors in the market currently can be reconfigurable. Secondly, there is a need to design a microprocessor which can be used freely for academic purposes. Thus, in this study, we will focus on the designing of a microprocessor that is reconfigurable, easily understood and freely available for academicals purposes. Methodology will describe way on how this project will be carried out. There are three main steps to be taken which are: 1) Studying the SimpleScalar instruction set architecture; 2) Programming and simulating by using VHDL programming language 3) Implementing the SimpleScalar architecture in VHDL and FPGA. In the Discussion, a detail contents regarding the project will be explained. Contents included are SimpleScalar's instruction format, register and operation cycle, software and hardware used in the project, the SimpleScalar implementation in VHDL and VHDL simulation. The further details will be discussed later. Finally, this report is concluded in the Conclusion. Recommendations describe the suggestions that can be done to the current project to improve them in the future.